Analisis Yuridis Pelaksanaan Putusan Perkara Waris dengan Obyek Sengketa yang Telah Memiliki Sertifikat Hak Milik - Suhardhono Suhardhono (Syntax Idea)
This research aims to analyze the legal aspects in the implementation of inheritance case decisions involving disputed properties that already have a property ownership certificate. The main focus of this research is to identify challenges and obstacles that may arise in the implementation of such decisions. The research method used is a normative analysis approach, which involves examining relevant laws and regulations, related jurisprudence, as well as relevant documents. The research findings indicate that the implementation of inheritance case decisions involving disputed properties with existing property ownership certificates involves a series of complex legal processes. The main challenge lies in harmonizing the court's decision with the validity of the previously issued property ownership certificate. Additionally, it is important to consider the rights of the parties involved that are protected by the law. This research also highlights the need for practical guidance or guidelines for parties involved in the implementation of such decisions, including judges, lawyers, and other relevant parties. These recommendations are expected to make a positive contribution to improving justice and effectiveness in resolving inheritance disputes involving properties with ownership certificates in the future.